Nurse Perception and Patient Satisfaction Toward About Hospital Sharia Standard Implementation at Inpatient Departement of Klaten Islamic Public Hospital - Sari, Hajar Fatma; Aini, Qurratul; Sundari, Sri; Sumarwanto, Edi (Universitas Aisyah Pringsewu, 2022)
The DSN MUI Sharia Hospital Standard is the first official Sharia Hospital standard in the world. Klaten Islamic Public Hospital has implemented the Syariah Hospital standard from National Sharia Board-Indonesian Council of Ulama (DSN-MUI) since 2019. The implementation of these standards was expected to have a good impact on patients and nurses. This study aims to determine the perceptions of nurses on the implementation of sharia standards and the relationship between the implementation of Islamic hospital standards and the level of patient satisfaction with sharia standards. This research used quantitative method. The study design was cross-sectional with purposive sampling that included 78 nurses and 263 patients. The inclusion criterion for nurses was to work in an inpatient ward with a minimum service period of 2 years. Exclusion criteria was nurses in isolation wards and intensive rooms. The inclusion criteria for patients were inpatients with a Muslim religion with a minimum length of stay of 2x24 hours, and the exclusion criteria were limited communication with the patient. The data were collected using the nurse's perception questionnaire, the patient implementation questionnaire and the patient satisfaction questionnaire which was tested for validity using the Pearson correlation formula, the reliability test used the Cronbach alpha formula. 10.5% of the nurses had a fairly good perception and 89.5% had a good perception of the implementation of the Sharia Hospital standards, and there were no significant differences between the various characteristics of the respondents (gender, age, education, workplace, length of work, position). 0.3% of patients stated that the implementation of sharia standards was still lacking, 5.5% said it was sufficient and 94.2% said it was good. 8.8% of patients are quite satisfied and 91.2% of patients are satisfied with sharia services at the Klaten Islamic General Hospital, there is no difference in satisfaction scores on various characteristics of patient respondents (gender, age, education, place of care, person in charge of costs, choice of coming, pathway admission to hospitalization, history of treatment, prayer habits, knowledge of Sharia Hospital). There is a significant relationship between the implementation of sharia services and patient satisfaction with a moderate level of strength. Most of the inpatient nurses have a good level of perception of the implementation of sharia standards at the Klaten Islamic Public Hospital, there is no difference in the level of perception among the demographic characteristics of nurses. Most of the patients considered the implementation of the Sharia Hospital standard had been done well and were satisfied with the service. There is a significant relationship between the implementation of sharia services and patient care with moderate strength. There is no difference in the level of satisfaction in all demographic characteristics of the patients. It shows that the implementation of sharia hospital standard is acceptable by inpatient nurses and patients at Klaten Islamic Public Hospital.